A digital image encryption algorithm based on chaotic mapping - Deng, Zhijuan; Zhong, Shaojun (Journal of algorithms & computational technology, 2019)
In this article, we introduced a digital image encryption algorithm based on the chaotic mapping designed by Xiong et al. In their paper, the authors theoretically analyzed the algorithm and pointed out that the algorithm did not need to have the prior knowledge of the orbital distribution and one can select any chaotic model. In this way, the algorithm greatly expanded the cryptographic space and greatly reduced the number of iterations of the mapping. Since the algorithm has many characteristics, for instance, it is sensitive to the secret key, its key space is big, the pixel is well distributed after being encrypted, etc., the security of the encrypted images can be assured effectively. However, since the algorithm applied the image scrambling for encryption, and did not take the chosen-plaintext attacks into consideration, the algorithm is relatively weak in resisting the chosen-plaintext attacks. Therefore, we put forward a kind of image replacement method based on chaos, which can resist the chosen-plaintext attacks. And the experimental simulation proves that this algorithm not only has many characteristics, for instance, it is sensitive to the secret key, its key space is big, the pixel is well distributed after being encrypted, etc., but also can resist the chosen-plaintext attacks effectively. In the meanwhile, the algorithm is very sensitive to the small changes of the plaintexts, and its encrypted images will completely lose the features of the original ones.